Two color morphs of the pelagic yellow-bellied sea snake, pelamis platura, from different locations of Costa Rica: snake venomics, toxicity, and neutralization by antivenom - Lomonte, Bruno (2014)
artículo (preprint) -- Universidad de Costa Rica, Instituto de Investigaciones Clodomiro Picado, 2014